The Improvement of Mathematics Achievement by The Use of an Integral Task Module - Atik Widiyawati (IAIN Salatiga, 2018)
This current class action research aims at the improvement of learning achievement on the topic of integral by the use of task module. A learning model is one factor affecting students’ achievement. The students’ daily learning achievement of grade XII TPHP D SMK (Public Vocational High School) I Bawen has not met the school minimum standard. It can be seen from the students’ performance that they are not motivated, enthusiastic, and active during Mathematics learning process, and their learning outcome has not fulfil the optimal standard. It remains under 75 as the minimum of school learning completeness (KKM) of 75. So that, it requires the implementation of learning model that can improve students’ learning achievement by using task module on the integral topic discussion. Notably, this research occupies the method of CAR (Class Action Research) through two cycles. Each cycle includes four stages namely planning, action, observation, and reflection. Further, the data are analysed quantitatively (learning scores) by providing descriptive analysis, and the qualitative data are in the form of information that describes students’ expression upon their understanding of the learning subject (cognitive), students’ attitude toward the new learning method, their activities in the learning, attention, enthusiasm in learning, confidence, learning motivation, etc. The result concludes that each cycle displays the improvement of learning achievement in which respectively the percentages are 30% in the first cycle and 93,33 in the next one. In the first cycle, there are 21 students getting lower scores under 75, and the class average point is 59,467. Whereas, in the cycle II, only 2 students achieve the scores below 75 by the class average point of 84,33. Thus, this research defines: 1) the use of module improves learning achievement on the integral topic discussion; 2) the learning activities transform from teacher centred into interactive.